HAKIKAT HIDUP MANUSIA DENGAN SESAMANYA DALAM TEMBANG MACAPAT - A Novin Budi Rossandy (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The goal in this study to determine the nature of human life in song Macapat. In this research is descriptive analytical method. Descriptive analytical method performed by describing the facts that exist in macapat, which is then followed by analysis.The object of this study is the book written by Sukatmi Susantina Song Macapat publication year, which included a song Mijil, Sinom, Maskumambang, Asmarandana, Dhandhanggula, Kinanthi, Gambuh, Durma, pickaxe, Magetruh, and Pocung. The song uses the Java language. The results showed that every human being with another human being should have a caring attitude and encourage one another. A nature that underlie the merits of Java man rooted in the Quran and Hadith. Through this analysis is expected in the Java community in particular can foster a caring attitude towards fellow human beings and appreciate the heritage of ancestors, especially closer to Allah SWT.